Dakwah Digital dalam Meme Ajakan Shalat Jum’at: Perspektif Semiotika - Sunaryanto Sunaryanto (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2022)
This study analyzes the meaning of digital da'wah in the Friday prayer invitation meme. This research was completed with a qualitative research approach with semiotic analysis which is part of the textual analysis of mass media. The findings of the research are digital da'wah signs in memes asking for Friday prayers such as caps, white koko clothes, mics, headscarves, Al-Qur'an etc. The digital da'wah signifiers in the meme are Rhoma Irama, Joko Widodo, Prabowo Subianto, beautiful women, etc. The signified digital da'wah memes are piety, faith, politicization of religion, and political campaigns. The denotation meaning of digital da'wah in the meme is that a good leader even though he is busy does not leave the Friday prayer obligation. Friday prayer should be understood by Muslim men compared to Friday night worship (i.e husband and wife relationship). Its connotative meaning is that the Friday prayer is understood as an attempt to gain political masses. Friday prayers are considered as a way to be handsome in this world only and not handsome in the hereafter. The conclusion is that digital da'wah in the invitation to Friday prayer can be interpreted in three contexts, namely Islam, culture and politics.